Her secret royal dilemma - Shaw, Chantelle (Harlequin presents, 2022)
"Moments from drowning, Prince Eirik is saved by mysterious Arielle Tremain. Royal duty dictates that he ignores their instant attraction. But he can offer the mesmerizing marine conservationist her dream job--in his kingdom... After a lifetime spent paying for her father's crimes, Arielle can't believe Eirik's generosity. Or that a future monarch desires her. So, when he seeks her out, Arielle faces the ultimate dilemma: indulge in this rare irresistible connection, knowing her past could taint Eirik's future...or walk away from the only man who really sees her?" -- Page [4] cover.